Analysis Of The Impact Of M-Banking Utilization On The Community In Patamuan Sub-District - Sartika, Sartika; Syamsurizal, Syamsurizal (Institut Agama Islam Sumatera Barat, 2023)
The development of information and communication technology (ICT) has changed the way people interact, including in terms of financial transactions. One of the significant innovations in the banking industry is the introduction of mobile banking services or M-banking. The use of M-Banking has brought about changes in people's financial behavior in the Patamuan District. Prior to the adoption of M-Banking, banking activities involving cash deposits, withdrawals, or transfers of funds required a physical presence at a bank or ATM machine. The use of M-Banking has had a positive impact on the people in Patamuan District. This service provides better accessibility to banking services, facilitates transactions, and enhances efficient financial management. In the economic aspect, the use of M-Banking has increased financial inclusion in Patamuan District. In addition to the positive impacts, there are also challenges and obstacles faced in using M-banking in the Patamuan District. Some of the obstacles or challenges that may have a negative impact are limited internet access, because several areas in Patamuan sub-district have limited internet access because the area is rather remote. There are three ways of data analysis techniques used, namely data reduction, data presentation, drawing conclusions. . The instruments used were observation, documentation and interviews.